Antrodia cinnamomea is a potentially effective complementary medicine for adjuvant therapy against breast cancer with bone metastasis: A case report. Issue 27 (2nd July 2020) - Long, Huei; Hu, Chi-Tan; Prijatelj, Vesna; Weng, Ching-Feng
Abstract: Rationale: Palbociclib (PAL) is a first-in-class selective inhibitor of the cyclin-dependent kinases 4 (CDK4) and CDK6 and is indicated for the treatment of hormone receptor (HR)-positive/human epidermal growth factor receptor 2 (HER2)-negative metastatic breast cancer (MBC) in combination with fulvestrant (FUL) in postmenopausal women. Antrodia cinnamomea (AC), a well-known Chinese folk medicine in Taiwan, possesses numerous biological capabilities, most notably an anti-tumor effect. However, the clinical use of AC as complementary medicine combined with adjuvant therapy is unexplored. In this case report, we evaluated AC combined with PAL plus FUL to reduce the tumor burden in an MBC patient. Patient concerns: A Slovenian woman diagnosed with relapsed bone metastases of breast cancer (BC) was unable to undergo surgery and refused radiation therapy due to fear of side effects; she also feared the side effects of adjuvants. However, she was eager to live with a high quality of life. Diagnosis: Stage IV, HR-positive/HER2-negative BC with relapse of bone metastases. Interventions: After diagnosis of relapse of bone metastases, she received adjuvant with PAL plus FUL. Additionally, she chose to take AC orally (10 g/d). Outcomes: The pain was mostly relieved, and the side effects of adjuvant therapy reduced. Magnetic resonance imaging revealed reduction of tumor size at the fifth month of adjuvant therapy plus AC. After 14 months of adjuvant therapy plus AC, the tumors at the thoracic vertebrae T1 and T3 were found to have shrunk from 35.2 and 12.0 mm to 28.1 and 9.9 mm, respectively. Remarkably, no further metastases were observed. Lessons: According to the circulating tumor cells (CTCs) test data, AC had better anti-tumor efficacy on active tumor cells than PAL plus FUL. Thus, AC could be an effective complementary medicine for adjuvant therapy in patients with HR-positive/HER2-negative MBC. Interestingly, continued elevation of carcinoma antigen 15-3 and lactate dehydrogenase levels but decreasing levels of alkaline phosphatase were observed, which may be indicative of the potent efficacy of treatment resulting in massive tumor cell death. The CTCs test may be a sensitive approach to monitor the progression of BC and subsequently evaluate the efficiency of therapy.